The Relationship Between Organizational Participation and Organizational Adaptability Among the Staffs of Imam Khomeini Hospital in Tehran, Iran - Azam Hosein Alizadeh; Mohammad Ali Abbasi Moghadam (Tehran University of Medical Sciences, 2012)
Background and Aim: Changes in political, economic, social, scientific and technological circumstances have a major impact on organizational performance. In such circumstances, the success of organizations depends on their ability to cope and adapt to changing environmental factors. This study investigated the relationship between organizational participation(team orientation, capability development and empowerment) and the organizational adaptability (change, customer orientation and organizational learning) in Imam Khomeini Hospital staff. Materials and Methods: This cross-sectional study was performed on 114 staffs of Imam Khomeini hospital, Tehran University of Medical Sciences who were selected by random sampling. Data were collected by Denison questionnaire (2006 version), which was confirmed validity and reliability. Data were analyzed with spss17 and statistical methods like the mean, standard deviation and correlation coefficients. Results: The results showed that the rate of the organizational involvement and adaptability of the staffs was 53.44% and 52.37% respectively. The Pearson correlation analysis showed a positive correlation coefficient (p<0.01, r=0.743) between two variables of organizational involvement and adaptability. Conclusion: With increasing organizational involvement of the staffs increases their organizational adaptability